2010
DOI: 10.1007/s00404-010-1607-x
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in hybrid banking: attitudes of Swiss public umbilical cord blood donors toward private and public banking

Abstract: Purpose Umbilical cord blood (UCB) stored in public inventories has become an alternative stem cell source for allogeneic stem cell transplantation. The potential use of autologous UCB from private banks is a matter of debate. In the face of the limited resources of public inventories, a discussion on ''hybrid'' public and private UCB banking has evolved. We aimed to explore the attitudes of the donating parents toward public and private UCB banking. Study design and methods A standardized, anonymous questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 15 publications
1
31
0
1
Order By: Relevance
“…[10][11][12][13] One driver for these models is to improve the financial viability of the CBBs. A number of models for combined banking have been developed, including joint marketing of separate banking operations, opportunities to split units for private and public use, and the offer to initially bank units as either public or private, but with the potential of converting their status at a later date or event.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] One driver for these models is to improve the financial viability of the CBBs. A number of models for combined banking have been developed, including joint marketing of separate banking operations, opportunities to split units for private and public use, and the offer to initially bank units as either public or private, but with the potential of converting their status at a later date or event.…”
Section: Discussionmentioning
confidence: 99%
“…This view is supported by the fact that there are an estimated 800,000 cords stored in private banks, which far exceeds that number of cords available for public access (Gluckman et al 2011;Manegold et al 2011). To date, however, there has been a paucity of empirical research into prospective mothers' motives for and decisions about opting either to donate or store UCB.…”
Section: Introductionmentioning
confidence: 91%
“…Given the substantial cost and low probability of using the product, the American Academy of Pediatrics, the American Society of Blood and Marrow Transplantation and the Society of Canadian Obstetricians and Gynecologists have clear position statements recommending against elective private UCB banking unless a family member is at high risk of needing a transplant in the future 13–15. Furthermore, critics have suggested that private UCB banks may overemphasise unproven possible future indications beyond HSCT 2 14…”
Section: Benefits and Limitations Of Private Ucb Banks In Making Ucb mentioning
confidence: 99%
“…A hybrid (or dual) UCB bank is a new model of UCB banking in which elements of private and public banking coexist 2 20. For the purposes of this discussion, a hybrid UCB bank is a private institution in which an UCB product is stored for possible public or private use.…”
Section: Hybrid Ucb Banksmentioning
confidence: 99%
See 1 more Smart Citation